Review of Health Law on Victims of Violence by Narcissistic Personality Disorder Sufferers from Human Rights and Bioethics Perspectives - Novita Andrayani Susanti; Bagiastra I Nyoman (Dinasti Research, 2025)
This study aiming For analyze aspect law health related to victims of violence committed by sufferers Narcissistic Personality Disorder (NPD) from perspective Right Basic Human rights and bioethics . Violence committed by individuals with NPD giving rise to multidimensional challenges , both from aspect law , health , and ethics . In context law health , important For ensure victims ' rights to protection and recovery health , at the same time ensure perpetrator get proper handling with condition psychological approach . human rights based emphasizes justice and equality in legal process and services health , while bioethics underline the principles of beneficence, non-maleficence, autonomy, and justice in handle case This . This Research use legal normative method with approach conceptual and case study results show that enforcement law based on human rights and bioethics can strengthen protection towards the victim at once push rehabilitation the perpetrator , so that create balance between justice retributive and restorative